Aktivitas Antioksidan Dan Sifat Organoleptik Teh DaunKelor Dengan Variasi Lama Pengeringan Dan Penambahan Kayu Manis Serta Cengkeh Sebagai Perasa Alami - Indriyani, Eka Datik, Dra. Aminah Asngad, M.Si (2015)
A new innovation in the manufacture of tea is by using Moringa leaf and with the addition of Cinnamon and cloves as natural flavourings. Moringa leaves contain vitamin A and C and also high compound flavonoid so that good for processed drink. The Cinnamon and clove was contains essentials oil eugenol which has a form of natural taste so good for the addition as flavourings. The purpose of this study to determine the antioxidant content and organoleptic test of Moringa tea leaves was given variation drying time Cinnamon addition and also cloves as natural flavourings. This study was used method RAL (Complete Random Device) factorial pattern by 2 factorial, first factorial that was Cinnamon and Clove addition ((0,25 g : 0,5 g (1 : 2), 0,5 g : 0,25 g (2 : 1)), and the second factorial of old drying variation that was during 40 minute, 80 minute and 120 minute. The highest antioxidant contain on A3B1 as miuch as 53,48% on 40 minutes drying time and 0,5 g and also 0,25 g Cinnamon Addition, lower result antioxidant contain on A2B1 as much as 44,3 % on 40 minutes srying time and 0,25 g Cinnamon addition and also 0,5 clove addition. Tea leaves organoleptic test owning energy accept liking was bold tan, adorous Cinnamon, feel fresh.